“Menyama Braya”: Pondasi Utama Relasi Dialog Agama-Agama di Desa Dalung, Bali - Ferdinand Ludji; David Samiyono; Izak Y.M. Lattu (Universitas Negeri Medan, 2020)
The purpose of this study is to describe and analyze the life values of the Balinese